Efforts to Foster Students’ Ecological Awareness Through an Ecopedagogical Approach in Social Studies at SMPN 4 Parepare - Muhammad Hidayat; Zurahmah Zurahmah; Nurleli Ramli; Fuad Guntara (STKIP Taman Siswa Bima, 2025)
This study uses a descriptive qualitative approach with a case study design to examine the implementation of ecopedagogical-based learning in Social Studies (IPS) at SMP Negeri 4 Parepare., focusing on its contribution to raising students' ecological awareness. Ecopedagogical-based learning integrates classroom theory with practical environmental experiences, encouraging students to not only understand environmental issues but also take responsibility for environmental conservation. At SMP Negeri 4 Parepare, the application of this approach through Project-Based Learning (PBL) and contextual learning methods has proven to significantly enhance students' ecological awareness, as seen in activities like tree planting and waste management. However, the implementation of this learning approach faces challenges, such as limitations in resources, funding, and curriculum time. Despite these obstacles, the school has worked to address these challenges by adopting creative approaches, such as collaborating with external organizations and utilizing more flexible learning methods. Student involvement in ecopedagogical-based activities, such as the